2016
DOI: 10.1111/iju.13184
|View full text |Cite
|
Sign up to set email alerts
|

Changes of sexual function and perception in Japanese men: A 15‐year cross‐sectional community‐based study

Abstract: Objectives: To investigate the longitudinal changes of sexual function of Japanese men. Methods: From 1992 to 1993, we carried out a cross-sectional community-based study on sexual function in Japanese men aged 40-79 years. After 15 years, a followup study was carried out to determine longitudinal changes of their sexual function. Of the 319 participants in the initial study, 135 participated again in the follow-up study. Sexual function was assessed using the same validated questionnaire in the two studies.Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Dietary supplements for sexual enhancement were most used among males aged 20–29 years, with a decreasing trend according to age advancement, even though the prevalence of erectile dysfunction (ED) increasing in correlation to age has been previously reported [22,23,24]. The proportion of moderate-to-severe ED among men who lived with their spouses varied from 1.8% in the age group of 20–29 years to 64.3% in those over 70 years [22].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplements for sexual enhancement were most used among males aged 20–29 years, with a decreasing trend according to age advancement, even though the prevalence of erectile dysfunction (ED) increasing in correlation to age has been previously reported [22,23,24]. The proportion of moderate-to-severe ED among men who lived with their spouses varied from 1.8% in the age group of 20–29 years to 64.3% in those over 70 years [22].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical approach to SED is still to be defined, as only few studies have evaluated non-ED conditions. A recent 15-year observational study conducted in Japanese men showed an association between penile rigidity decrement in each decade of life (40 s, 50 s, 60 s, and 70 s) and dissatisfaction with their own sexual function (except from men 70 years and above); this association was shown whether or not patients met the criteria for classical ED [26]. An objective quantification of penile rigidity (thus to find even slight differences in rigidity among the spectrum of non-ED patients) could be obtained through imaging techniques, such as virtual touch tissue quantification (VTTQ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 398 patients who originally had impaired preoperative sexual function (IIEF-5 score, <12 points) and 38 patients who did not answer the questionnaire 12 months after surgery were excluded. Erectile dysfunction severity is typically classified into 5 categories based on IIEF-5 scores: severe (5-7), moderate (8)(9)(10)(11), mild-to-moderate (12)(13)(14)(15)(16), mild (17)(18)(19)(20)(21), and no ED (22)(23)(24)(25). The average IIEF-5 score for a 50-year-old Japanese man has been reported as 16 points.…”
Section: Study Populationmentioning
confidence: 99%